Pengaruh Digital Management Accounting Tools (DMAT) Terhadap Efisiensi Operasional UMKM Di Era Industri 5.0: Studi Kasus Kota Bengkulu - Nafilatul Wilda Wilda; Nopi Tikasari (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study examines the effect of Digital Management Accounting Tools (DMAT) on the operational efficiency of Micro, Small, and Medium Enterprises (MSMEs) in Bengkulu City in the era of Industry 5.0. The low adoption of digital accounting applications due to limited digital literacy, human resource quality, and technical support constitutes the main problem underlying this research. A quantitative approach was employed using an explanatory case study design involving 120 MSME owners selected through proportional random sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The results demonstrate that DMAT has a positive and significant effect on MSME operational efficiency. Furthermore, managerial digital capability is proven to partially mediate the relationship between DMAT and operational efficiency. In other words, the effectiveness of DMAT implementation in improving operational efficiency is optimized when supported by strong managerial digital capabilities. These findings reinforce the relevance of the Technology Acceptance Model (TAM) in the context of MSME digital transformation and provide practical implications for policymaking and strategies to accelerate regional MSME digitalization.